2020
DOI: 10.7717/peerj.9016
|View full text |Cite
|
Sign up to set email alerts
|

Additions to the phylogeny of colubrine snakes in Southwestern Asia, with description of a new genus and species (Serpentes: Colubridae: Colubrinae)

Abstract: Reptiles are still being described worldwide at a pace of hundreds of species a year. While many discoveries are from remote tropical areas, biodiverse arid regions still harbor many novel taxa. Here, we present an updated phylogeny of colubrid snakes from the Western Palearctic by analyzing a supermatrix of all available global snake species with molecular data and report on the discovery of a new genus and species of colubrine snake from southeastern Iran. The new taxon, named Persiophis fahimii Gen. et sp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Furthermore, we found that short lateral processes lead to a more pointed snout, thus a projected rostrum, a condition also commonly used as a key character to separate Argyrogena from Platyceps (see e.g. Rajabizadeh et al 2020). However, a projected rostrum of variable expression and a countersunk lower jaw is also reported for different Platyceps species by Schätti et al (2014; see also comments below).…”
Section: Comparision Of Osteologymentioning
confidence: 56%
See 2 more Smart Citations
“…Furthermore, we found that short lateral processes lead to a more pointed snout, thus a projected rostrum, a condition also commonly used as a key character to separate Argyrogena from Platyceps (see e.g. Rajabizadeh et al 2020). However, a projected rostrum of variable expression and a countersunk lower jaw is also reported for different Platyceps species by Schätti et al (2014; see also comments below).…”
Section: Comparision Of Osteologymentioning
confidence: 56%
“…In their study on Western Palearctic colubrid snakes, Rajabizadeh et al (2020) provided a comparative morphological table with eight characters for colubrine genera of India, Central and Western Asia and North Africa. All these characters were identical for Wallaceophis and Wallophis and for Argyrogena and Platyceps as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, all phylogenetic analyses (MP, NJ, and BI) support the monophyletic status of the genus Lytorhynchus from Asia and Africa based on the concatenated analysis and the 12S rRNA gene separately. Previous assemblage studies suggested the monophyly of most members within subfamily Colubrinae based on molecular DNA sequences and morphology (McDowell 1987;Rossman and Eberle 1977;Heise et al 1995;Kraus and Brown 1998;Vidal et al 2000;Kelly et al 2003;Rajabizadeh et al 2020). Furthermore, Tamar et al (2016) referred to the monophyly of Rhynchocalamus, which had separated from Lytorhynchus during the Late Oligocene at ca.…”
Section: Discussionmentioning
confidence: 98%
“…Knowledge of the snake fauna of Middle and Southwest Asia (here considered the countries of Afghanistan, Iran, western China, Mongolia and the former Soviet Middle Asian republics fide Berg, 1931 ; Geptner, 1938 ; Chernov, 1949 ) has improved over the past decade as researchers continue to contribute species descriptions, range extensions, and natural history observations ( Wagner et al, 2016a ; Rajabizadeh, 2018 ; Shestopal & Rustamov, 2018a ; Shestopal & Rustamov, 2018b ; Orlov et al, 2018 ; Asadi et al, 2019 ; Rajabizadeh et al, 2020 ; Eskandarzadeh et al, 2020 ; Chen et al, 2021 ). Biogeographically, most snakes inhabiting Middle–Southwest Asia are elements of the Palearctic; however, a few species traditionally associated with the Indo-Malayan (Oriental) realm reach their westernmost distributional limits in this region ( Wagner et al, 2016b ; Orlov et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%